Particulate emissions in an engine fueled with biodiesel/Diesel blends at different fuel injection system configurations - Sala,José Antonio (2022)
ABSTRACT: The present study aimed to evaluate the particulate emissions in a Diesel engine with an electronic injection system using different biodiesel blends and variations in the fuel injection point and volume, comparing it with the MAR-1 standard. The particulate emissions are analyzed using a two-factor (12×8) completely randomized design that resulted from the interaction of three biodiesel/Diesel blends, two injection point configurations, two fuel injection volumes and eight crankshaft speeds, with 30 repetitions. According to the results, the particulate emissions meet the requirements established by the MAR-I standard when the engine operates at the original factory settings, fueled with blends containing up to 30% of biodiesel. With the engine angular speed at maximum torque (1,500 rpm), the injection point advanced and the increase in fuel volume, the particulate emissions increased by 115% and 314% for the 10 and 30% biodiesel blends, respectively, regarding the engine operating with the original settings.